2023
DOI: 10.1021/acs.jmedchem.3c00875
|View full text |Cite
|
Sign up to set email alerts
|

Structural Mechanism and Inhibitors Targeting EGFR Exon 20 Insertion (Ex20ins) Mutations

Hao Chen,
Shiliang Hu,
Adam V. Patterson
et al.

Abstract: Epidermal growth factor receptor (EGFR) targeted therapy is one of the most important and effective strategies to combat EGFR mutant nonsmall-cell lung cancer (NSCLC). However, a substantial number of patients bearing EGFR exon 20 insertion (Ex20ins) mutations respond poorly to common EGFR targeted therapies. This clinical need remained unmet until recently, when the EGFR Ex20ins mutation inhibitor mobocertinib was approved by the FDA. Despite this progress, the structural mechanisms of EGFR Ex20ins mutation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that researchers create appropriate drugs for different mutations based on homology modeling and simulation experiments ( 103 ). In future work, focus should be placed on exploring structural changes to determine which mutation sites render patients more sensitive to EGFR TKIs, whether accompanied by alterations in other pathways, to provide a basis for prognosis assessment and drug decision-making ( 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that researchers create appropriate drugs for different mutations based on homology modeling and simulation experiments ( 103 ). In future work, focus should be placed on exploring structural changes to determine which mutation sites render patients more sensitive to EGFR TKIs, whether accompanied by alterations in other pathways, to provide a basis for prognosis assessment and drug decision-making ( 104 ).…”
Section: Discussionmentioning
confidence: 99%